Brazilian Public Health System protocol for the diagnosis, treatment, and clinical monitoring of acute ischemic stroke - Rocha, Aline; Pinto, Ana Carolina Pereira Nunes; Stein, Cinara; Colpani, Verônica; Gräf, Débora; Dorneles, Gilson; Belli, Karlyse Claudino; Parahiba, Suena; Falavigna, Maicon; Martins, Sheila Ouriques; Atallah, Álvaro Nagib (Arquivos de Neuro-Psiquiatria, 2025)
The Brazilian Ministry of Health has issued new recommendations for the management of patients with acute ischemic stroke. The protocol covers aspects related to diagnosis, treatment, and patient monitoring, expanding the available treatment options for patients treated within the Brazilian Public Health System (Sistema Único de Saúde – SUS, in Portuguese). This article discusses some of the recommendations presented in the current Clinical Practice Protocol, aiming to spread awareness of the document's updates and assist healthcare professionals and services in implementing these recommendations.
Keywords: Ischemic Stroke; Clinical Protocols; Tissue Plasminogen Activator; Thrombectomy; Public Health